A survey of practice patterns for adaptive particle therapy for interfractional changes - Trnkova, Petra; Zhang, Ye; Toshito, Toshiyuki; Heijmen, Ben; Richter, Christian; Aznar, Marianne C.; Albertini, Francesca; Bolsi, Alessandra; Daartz, Juliane; Knopf, Antje C.; Bertholet, Jenny (Physics and imaging in radiation oncology, 2023)
•84% of particle therapy centres adapt plans for inter-fractional changes.•All users of adaptive particle therapy except two perform offline plan adaptation.•68% of centres had plans to implement or improve their adaptive workflow.•The lack of integrated workflows was the main limitation to implementation.•Broad-scale implementation needs joint efforts of industry, research and clinics. Anatomical changes may compromise the planned target coverage and organs-at-risk dose in particle therapy. This study reports on the practice patterns for adaptive particle therapy (APT) to evaluate current clinical practice and wishes and barriers to further implementation. An institutional questionnaire was distributed to PT centres worldwide (7/2020–6/2021) asking which type of APT was used, details of the workflow, and what the wishes and barriers to implementation were. Seventy centres from 17 countries participated. A three-round Delphi consensus analysis (10/2022) among the authors followed to define recommendations on required actions and future vision. Out of the 68 clinically operational centres, 84% were users of APT for at least one treatment site with head and neck being most common. APT was mostly performed offline with only two online APT users (plan-library). No centre used online daily re-planning. Daily 3D imaging was used for APT by 19% of users. Sixty-eight percent of users had plans to increase their use or change their technique for APT. The main barrier was “lack of integrated and efficient workflows”. Automation and speed, reliable dose deformation for dose accumulation and higher quality of in-room volumetric imaging were identified as the most urgent task for clinical implementation of online daily APT. Offline APT was implemented by the majority of PT centres. Joint efforts between industry research and clinics are needed to translate innovations into efficient and clinically feasible workflows for broad-scale implementation of online APT.